PENGARUH KARAKTERISTIK PERSONAL AUDITOR TERHADAP PERILAKU MENYIMPANG DALAM AUDIT - Cahyadini, Erymesha Putri; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research to examine the influence of auditor personal characteristics to the deviant behavior in audit. The deviant behavior in audit is measured by locus of control, performance, organization committment, and turnover intention. This research is a quantitative research. The population is thw audit board of republic of Indonesia East Java province representative and the sample collection technique has been done by using purposive sampling method. 56 respondents have been selected as samples. The data collection technique has been carried out by using survey method. The data is the primary data in the form of questionnaires which have been issued to the respondents. The analysis method has been done by using multiple lienar regressions and the SPSS (Statistical Product and Service Solutions) 20.0 version. The deviant behavior in audit has been done by the person to cover the weaknesses he or she has and there is high opportunity to conduct deviant behavior in order to stay in the related organization and does not loss his or her job.Keywords: locus of control, performance, organization committment, turnover intention, deviant behavior in audit